EFFECTS OF TREADMILL RUNNING WITH AND WITHOUT WEIGHT ON EXPLOSIVE POWER AMONG COLLEGE MEN ATHLETES (International Journal of Food and Nutritional Sciences, 2022)
The purpose of the study was to find out the effects of treadmill running with and without weight on explosive power among college men athletes. For the purpose of the study, random group design was employed. Randomly selected college level men athletes (N=60) were divided into three groups consisting of 20 in each group